PERAN DPD DALAM PENERAPAN ASAS DESENTRALISASI PADA SISTEM OTONOMI DAERAH - Bayu Dwiwiddy Jatmiko (Legality : Jurnal Ilmiah Hukum, 2016)
According to the Indonesian constitutional authority of DPD system is still very limited. All tasks and authority of DPD limited to the aspects that are closely linked with the area. Nevertheless, the Council position is not aligned with the Parliament; therefore need to be reviewed in the Council's role in the decentralized system of regional autonomy. So as to encourage the establishment of legislation to the maximum this is more favorable to the region and the well-being of the people in the area.